Towards a dynamic knowledge-based theory of the firm: an activity system perspective - KHADIR POGGI, YASMINA (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2018)
The question of human knowledge in organisations has long occupied philosophers and sociologists of science before attracting organisational researchers' attention more recently. Indeed, how knowing and knowledge emerge and / or are created has become a central concern in organisations, and research interests in the knowledge-based view of the firm have accelerated. Addressing the challenges posed by both theorists and practitioners over the past 20 years, this dissertation empirically investigates the emergence and / or creation of knowing and knowledge within asset management firms. The continued interest in the field has been linked to the constant attempts in understanding the mechanisms and dynamics supporting organisational knowing (OK) and knowledge emergence and / or creation. The existing contributions in the field are partial, prescriptive and fragmented. While the concepts and principles associated with OK, underpinned by a broad range of theoretical and practical knowledge-based approaches and prescriptive models in the literature, current research paradigms do not provide an adequate methodological perspective to explore the processes involved in organisational knowing and knowledge emergence and / or creation. To address this problem, this thesis proposes a novel methodological approach that uses activity theory. A pre-requisite was set to identify a unifying terminology to qualify asset management firms in terms of knowledge-based characteristics. The results from this first step informed a conceptual framework rooted in activity theory and substantiated by empirical evidence. Relying on a combination of epistemological knowledge approaches and organisations as activity systems, the mechanisms and dynamics involved in organisational knowing and knowledge emergence and /or creation are explored. Drawing on organisational knowing and knowledge and activity theory literatures, this exploratory and explanatory thesis has attempted to suggest a holistic and dynamic knowledge-based theory of the firm that is operational. This approach rests on envisaging the firm as an activity system dedicated to the understanding of cognitive developments at the social and personal levels. This thesis has developed a novel and unique conceptual perspective that does not separate theory and method. It is believed that this research may have far-reaching implications emerging from the comprehensive and novel approach integrating a theory of knowledge, a theory of the firm and an approach of activity theory grounded in critical realism.
A study of the mechanisms and dynamics underlying organisational knowledge and knowing emergence and creation in asset management firms using activity theory
APPROVED
Keywords: Organisational knowledge; Organisational knowing; Knowledge emergence; Knowledge creation; Activity theory; Theory of knowledge; Knowledge-based theory of the firm; Theory of organisations; Dialectic historical materialism; Critical realism; Qualitative study; Exploratory and explanatory study; Asset management